Nonbuoyancy density-driven convective mass and heat transfer : scaling analysis and solution methodology - Krantz, William B. (2013)
Density change during mass or heat transfer can cause convection in the absence of buoyancy forces. Prior studies have shown that this convection can be significant in the determination of diffusion coefficients and in the casting of polymeric membranes. Including this effect is challenging even for advanced numerical codes. A general methodology for obtaining the mass-average velocity for unsteady-state, one-dimensional, multicomponent mass and/or heat transfer circumvents the problem of numerically solving the coupled continuity equation. Scaling analysis permits assessing the importance of this convection for a generic equation-of-state. Numerical predictions for evaporation from a liquid layer for components having density ratios of 1:1 and 0.7:1 indicate that ignoring convection results in errors of 34% and 24% in the evaporation time and final thickness, respectively. This convection also influences the evaporation in the percutaneous application of cosmetics, medications, and insecticides, curing of paints, varnishes, and lacquers, and formation of thin films.